Effects of basal area on survival and growth of longleaf pine when practicing selection silviculture - Kara, Ferhat; Loewenstein, Edward F.; Brockway, Dale G. (Editorial CSIC, 2017)
Aim of study: Uneven-aged (UEA) management systems can achieve multiple-use objectives, however, use of UEA techniques to manage longleaf pine (Pinus palustris Mill.) forests are still open to question, because of the species’ intolerance of competition. It was our aim to examine the influence of different levels (9.2, 13.8 and 18.4 m2 ha-1) of residual basal area (RBA) on longleaf pine seedling survival and growth following three growing seasons.Area of study: This study was conducted at the Escambia Experimental Forest, located on the Southern Coastal Plain of Alabama, in the southeastern United States.Material and Methods: Selection silviculture was implemented with the Proportional-Basal Area (Pro-B) method. Prescribed burning was conducted before seed dispersal and in the second year after germination. Photosynthetically active radiation (PAR) was measured under the canopy in the study plots. Survival and growth of longleaf pine seedlings were observed for three growing seasons.Main results: An inverse relationship was found between the number of germinants and RBA, but the mortality of germinants and planted seedlings was not affected by RBA. At age three, an inverse relationship was observed between root-collar diameter (RCD) growth of the germinants and RBA, but RCD growth of planted seedlings was not affected by RBA. Most of the study plots contained more than the projected number of seedlings needed to sustain the target diameter structure.Research highlights: Long-term continuous monitoring of seedling development and recruitment into canopy is required to determine the efficacy of UEA management. However, current data suggest that UEA methods may be a viable alternative to the use of even-aged (EA) methods in longleaf ecosystems.
Keywords: Sustainability; Uneven-aged management; Forestry; Prescribed burning; Recruitment; SD1-669.5; Single-tree selection; Prescribed burning, Recruitment, Single-tree selection, Sustainability, Uneven-aged management; 15. Life on land